PRAKTIK DAN TANTANGAN MANAJEMEN MUTU TECHNOLOGY-ENHANCED LEARNING (TEL) DI SEKOLAH MENENGAH PERTAMA WILAYAH PEDESAAN - Saugadi Saugadi; Sitti Nuralan (LPPM Universitas Madako Tolitoli, 2026)
Technology-Enhanced Learning (TEL) is increasingly promoted as a strategic approach to improving learning quality; however, its implementation in rural lower secondary schools remains constrained, particularly from a quality management perspective. This study examines TEL quality management practices, identifies the challenges faced by schools, and analyzes the positioning of TEL within school planning, evaluation, and quality assurance systems. A qualitative multi-site case study design was employed across three public lower secondary schools in rural Galang District. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed thematically. Findings reveal that TEL practices in the studied schools have not been systematically integrated into school quality management frameworks. TEL planning remains adaptive and informal; instructional implementation is sporadic and largely teacher-centered; evaluation and monitoring lack formal structure; and quality assurance as well as sustainability rely heavily on individual teacher initiative and normative leadership support. These results indicate that TEL effectiveness cannot be ensured solely through technology availability, but requires a structured and sustainable quality management system. This study contributes a contextual conceptual model of TEL quality management that positions TEL as an integral component of school quality management, encompassing strategic planning, instructional implementation, evaluation and monitoring, and continuous quality assurance within rural school contexts.